Analysis of DFIG Wind Turbine During Steady-State and Transient Operation - Omer Elfaki Elbashir; Wang Zezhong; Liu Qihui (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In recent years, there has been a worldwide growth in the exploitation of wind energy. In the wind power industry, the majority of grid-connected wind turbines are equipped with doubly fed induction generators (DFIGs) because of their advantages over other wind turbine generator (WTG) systems. Therefore, much research effort has gone into the issues of modeling, analysis, control and grid integration of DFIG wind turbines. This paper deals with the modeling, analysis, and simulation of a DFIG driven by a wind turbine. The grid connected wind energy conversion system (WECS) is composed of DFIG and two back to back PWM voltage source converters (VSCs) in the rotor circuit. A machine model is derived in an appropriate reference frame. The grid voltage oriented vector control is used for the grid side converter (GSC) in order to maintain a constant DC bus voltage, while the stator voltage oriented vector control is adopted in the rotor side converter (RSC) to control the active and reactive powers. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5205